STRATEGI COPING KLIEN MUSLIMAH YANG MENJALANI REHABILITASI NARKOBA - Talitha Shabrina; Anisatul Mardiah; Fajar Tri Utami (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2018)
Human has competence to create something because human has motif or need. Every human has many needs have to be fulfilled. If needs are wanted not to be fulfilled, appear crisis in self. The crisis in self makes human to decide false choice in his life including drug misuse. In the context of drug client, coping strategy purposes to see to what extent dimension and consideration will be done in framework to choose better way to encounter all pressures such as problems when undergo rehabilitation, because every drug client has different ways to solve problematic in her life. Along undergo drug rehabilitation most subjects inclined to use type as coping strategy is emotion focused coping and one subject uses problem focused coping. This research used qualitative-descriptive type. The purpose of the research is to know type of coping strategy and behavior form from muslimah client to undergo drug rehabilitation. Subject of the research totals 4 people. Collecting the data method in this research used interview, observation and documentation. Data analysis used data reduction, presentation and verification as well as investigating validity of data to be done with extension of observation, data triangulation and member check.